Prostaglandin D2 amplifies lupus disease through basophil accumulation in lymphoid organs - Christophe Pellefigues (Nature Portfolio, 2018)
In a lupus environment, basophils accumulate in secondary lymphoid organs where they affect pathogenesis by stimulating autoantibody production. Here the authors show this accumulation is driven by PGD2-induced CXCR4 surface expression and trafficking of basophils.